Retrospective Analysis of 68 Hospitalized Patients with Epistaxis - Kaygusuz, İrfan; Karlıdağ, Turgut; Keleş, Erol; Yalçın, Şinasi; Alpay, Hayrettin Cengiz; Sakallıoğlu, Öner (Fırat University, 2004)
Objective: To discuss the etiology and the treatment of epistaxis which is common E.N.T. emergency in the light of literature, and to present the management of our clinic to patients with epistaxis. Materials and Methods: The charts of 68 patients with epistaxis who treated by hospitalized were investigated retrospectively. These patients were analyzed about their age, sex, and the month in which epistaxis happen, etiological factors, the necessity of blood transfusion, treatment methods and the duration of hospitalization. Results: 22 of 68 patients (32.3%) were female and remnant 46 patients (67.7%) were male, their age ranged 16 to 88 years old (mean age 56.79±17.30 years). The patients with epistaxis were applied to our clinic mostly in March (13.2%). The most common reasons of epistaxis were hypertension (30.8%) and nasal septal perforation (20.6%). The blood transfusion needed for 16 patients; while only one unit blood transfusion was delivered to 3 of these patients, 2-7 unit (averagely 2.61±1.38 unit) blood transfusion were delivered to other 13 patients. The duration of hospitalization were ranged 1 to 20 days (mean 5.94±2.68 days; 4.82±1.20 days for patient treated conservatively methods and 8.42±3.37 days for patients treated surgically methods.). Conclusion: Epistaxis is one of the most common E.N.T. emergencies. The patients should be considering important due to possible complications, and especially old patients should be treated by hospitalized. ©2004, Fırat Üniversitesi, Tıp Fakültesi

Amaç: Yaygın bir kulak burun boğaz acili olan epistaksisin etiyolojisi ve tedavisinin literatür ışığında tartışılması şe kliniğimizin epistaksisli hastaya yaklaşımının sunulması. Gereç ve Yöntemler: Kliniğimizde burun kanaması nedeniyle yatırılarak tedavi edilen 68 hastanın dosyaları retrospektif olarak yeniden incelendi. Hastalar yaş, cinsiyet, epistaksisin olduğu ay, etiyolojik faktörler, eşlik eden hastalıklar, kan transfüzyonu gerekli olup olmadığı, uygulanan tedavi yöntemleri ve hastanede kalış süresi bakımından analiz edildi. Bulgular: 68 Hastanın 22'si kadın (%32,3), 46'sı (%67,7) erkekti ve yaşları 16-88 yıl (ortalama 56.79±17.30 yıl) arasında değişmekteydi. Epistaksisli hastalar, en sık mart ayında (%13.2) kliniğimize müracaat etmişlerdi. Epistaksisin en sık nedeni hipertansiyon (%30.8) ve septal perforasyondu (%20.6). Hastaların 16'sına kan transfüzyonu gerekmişti. Bunlardan üçüne bir ünite, 13'üne ise 2-7 ünite (ortalama 2.61±1.38 ünite) kan transfüzyonu yapılmıştı. Hastaların 47'sine (%69,2) konservatif, 21'ine (%30,8) cerrahi tedavi uygulanmıştı. Hastanede kalma süreleri 1-20 gün (ortalama 5.94±2.68 gün; konservatif yöntemle tedavi edilenlerde 4.82±1.20 gün; cerrahi yöntemlerle tedavi edilenlerde 8.42±3.37 gün)) arasında değişiyordu. Sonuç: Epistaksis sık görülen kulak burun boğaz acillerindendir. Gelişebilecek komplikasyonlar nedeniyle hastalar önemsenmeli, özellikle yaşlı hastalar yatırılarak tedavi edilmelidir. ©2004, Fırat Üniversitesi, Tıp Fakültesi
Hastaneye Yatırılarak Tedavi Edilen 68 Epistaksisli Hastanın Retrospektif Analizi